Nitric acid trihydrate (NAT) formation at low NAT supersaturations - Voigt, C.; Schlager, H.; Luo, B. P.; Dörnbrack, A.; Roiger, Anke; Stock, P.; Curtius, J.; Vössing, H.; Borrmann, S.; Davies, S.; Konopka, P.; Schiller, C.; et al. (HAL CCSD, 2004)
International audience A polar stratospheric cloud (PSC) was observed on 6 February 2003 in the Arctic stratosphere by in-situ measurements onboard the high-altitude research aircraft Geophysica. Low number densities (~10 ?4 cm ?3 ) of nitric acid (HNO 3 ) containing particles ? probably NAT ? with diameters up to 6 µm were measured at altitudes between 18 and 20 km. These particles have the potential to grow further and to remove HNO 3 from the stratosphere, thereby enhancing polar ozone loss. Interestingly, the NAT particles formed in less than a day at temperatures T > T NAT ?3.5 K, just slightly below the NAT equilibrium temperature T NAT . This unique measurement of PSC formation at extremely low NAT saturation ratios ( S NAT ?11) constrains current NAT nucleation theories. In particular, NAT formation on ice can for certain be excluded. Conversely, we suggest that meteoritic particles may be favorable candidates for triggering nucleation of NAT at the observed low number densities.